SD L-filter for filtration of images corrupted by mixed noise in frequency domain - Hudec, Robert (Communications - Scientific letters of the University of Zilina, 2004)
Slower filter coefficients adaptation of adaptive LMS (Least Mean Square) filters in time domain can be improved by their constrained or unconstrained modifications, but not rapidly. Other alternative is its realisation in frequency domain, where filtered signal is de-correlated and adaptation algorithm converges faster. Based on idea of adaptation in frequency domain there was developed L-filter in frequency domain. To the group of adaptive non-linear digital filters belong adaptive L-filters (L–F), whose outputs are linear combination of order statistics. They have a simple design and they know how to adapt own coefficients to various noise types. For powerful suppression of mixed noise there was designed a signal-dependent filter structure, which consists of two L–Fs and one SID (Spatial Impulse Detector). The former suppresses noise in homogeneous regions, the latter preserves details of a filtered image. This paper is devoted to the design of SD LMS L–F structure in frequency domain, which uses the SMD detector (Spatial Median Detector). The aim of this design is to obtain optimal parameters of SD LMS L–F such as threshold, level and adaptation step or optimal weight coefficients.